Multiple description coding ghost imaging - Zhang, Yi; Zhang, Yunhe; Chang, Chen; Sun, Shuai; Liu, Weitao (Frontiers in Physics, 2023)
Ghost imaging(GI) reveals its exceptional superiority over conventional cameras in a range of challenging scenarios such as weak illumination or special waveband. For high-performance GI, it's vital to obtain a sequence of high-fidelity bucket signals. However, measurements may suffer from distortion or loss in harsh environments. Here we present multiple description coding ghost imaging, which rests on illumination consisting of different coding patterns to address this challenge. Experimental results indicate that the proposed method is capable of producing satisfactory image even when the sequence of bucket signals is incomplete or highly distorted.This method provides an encouraging boost for GI in practical applications.